MODEL PENGGUNAAN LAHAN DAN PERUBAHAN PENGGUNAAN LAHAN UNTUK BAHAN BAKU BIODISEL KELAPA SAWIT: STUDI KASUS DI KABUPATEN ROKAN HILIR - Laurinciana S. Sampebatu, Yandra Arkeman, Erliza Hambali, Vincent Gaspers, Bambang Hero Saharjo (Department of Agroindustrial Technology, Bogor Agricultural University, 2016)
Land use and land use change for palm oil plantation is having both positive and negative influence to the increase of CO2 emission. This research was intended to (1) Analyze land use change in such case of Rokan Hilir district between the year of 2009 and 2011; (2) Measure CO2 emission that produced by land use change for palm oil plantation, and (3) Designing a model of land use and land use change in order to minimize CO2 emission. Land use change was identified using GIS based analysis, while CO2 emission was measured by using IPCC 2006 method. The model of land use change was established through the method of Genetic Algorithm. The result of the research shows that net CO2 emission that produced during the year of 2009 to 2011 in Rokan Hilir district was 0.89 Mt/year. The additional area of 676 Ha for biodiesel feedsctock of palm oil was came from 169 gens of 13x13 matrix where produced negative emission value (carbon sequestration) of 0.067 Mt CO2e/year. This emission can be reduced significantly by changing land use as calculated using the model of land use change that developed is this research, where as the number of emission then will be 0.82 Mt CO2e/year.Keywords: carbon stock, CO2 emission, land use and land use change, palm oil, genetic algorithm